2019
DOI: 10.5380/rf.v50i1.61088
|View full text |Cite
|
Sign up to set email alerts
|

A NON-DESTRUCTIVE METHOD FOR ESTIMATING LEAF AREA OF Ceiba glaziovii (Kuntze) K. Schum.

Abstract: The determination of leaf area is of fundamental importance in studies involving ecological and ecophysiological aspects of forest species. The objective of this research was to adjust an equation to determine the leaf area of Ceiba glaziovii as a function of linear measurements of leaves. Six hundred healthy leaf limbs were collected in different matrices, with different shapes and sizes, in the Mata do Pau-Ferro State Park, Areia, Paraíba state, Northeast Brazil. The maximum length (L), maximum width (W), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Other research has also recorded greater variability for the product between length and width (Gomes et al 2020), the product between length and length (Ribeiro et al 2020b), the product between width and width (Oliveira et al 2019b), and observed leaf area (Donato et al 2020). The kurtosis coefficients of the variables of the present study showed that the frequency distribution was flatter than the normal distribution (Ribeiro et al 2020a).…”
Section: Discussionsupporting
confidence: 54%
“…Other research has also recorded greater variability for the product between length and width (Gomes et al 2020), the product between length and length (Ribeiro et al 2020b), the product between width and width (Oliveira et al 2019b), and observed leaf area (Donato et al 2020). The kurtosis coefficients of the variables of the present study showed that the frequency distribution was flatter than the normal distribution (Ribeiro et al 2020a).…”
Section: Discussionsupporting
confidence: 54%
“…The coefficient of kurtosis (k) value less than 3 (k<3) is an indicative that all analyzed variables had a platykurtic distribution, expected for a normal distribution. This behavior shows that the frequency distribution function of the variables is more flattened than the normal distribution (Ribeiro et al, 2020). This distance from a normal distribution observed in all variables (L, W, L.W, L.L, W.W, and LA) occurred due to deviations in the coefficients of asymmetry and kurtosis.…”
Section: Discussionmentioning
confidence: 76%
“…This same regression model was recommended to estimate the leaf area of other forest species, such as Combretum leprosum (LA=0.7103*L.W; Candido et al, 2013), Crotalaria juncea L. (LA=0.7390*L.W; Carvalho et al, 2017a), Tectona grandis L. f. (LA=0.4449*L.W; Braga et al, 2018), and Ceiba glaziovii (Kuntze) K. Schum. (LA=0.4549*L.W; Ribeiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…watering until signs of leaf wilting (SS) varied from 9.3% to 9.6%, before reirrigation, which demonstrates a reduction of about 20 and 50% in soil moisture, for plants grown under moderate water restriction and severe, respectively, when compared to the control treatment (Table 1). The water deficit in the soil is one of the main abiotic factors that affect the establishment and dynamics of plant species, affecting the growth rates and production of dry matter in the initial stage of plant development (Silva et al, 2013;Gratani, 2014;Ribeiro et al, 2019;Santos Júnior et al, 2020).…”
Section: Resultsmentioning
confidence: 99%